EFFECT OF LDR, CAR, BOPO AND INFLATION ON NPL - Rizal Abidi; Usman Sastradipraja (SEAN Institute, 2023)
This study aims to determine the effect of LDR, CAR, BOPO and inflation on NPLs. In this study, the author used quantitative research methods with descriptive and associative approaches. The population used in this study is all companies in conventional commercial banks listed on the Indonesia Stock Exchange (IDX) which presents complete and consistent data in the 2017-2021 period and has been listed aka gone public on the Indonesia Stock Exchange (IDX). The sampling technique used in this study is the Non Probability Sampling method. The results of this study state that the Loan to Deposit Ratio (LDR) has a significant effect on Non Performing Loans (NPL). Capital Adequacy Ratio (CAR) has a significant effect on Non-Performing Loans (NPLs). Operating Income Operating Costs (BOPO) have a significant effect on Non-Performing Loans (NPLs). Inflation shows insignificant against Non-Performing Loans (NPLs). And simultaneously that Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Operating Cost of Operating Income (BOPO) and Inflation have a significant effect on Non-Performing Loans (NPLs).